Effects of probiotic Lactobacillus brevis KB290 on incidence of influenza infection among schoolchildren: an open‐label pilot study. (1st December 2014) - Waki, N.; Matsumoto, M.; Fukui, Y.; Suganuma, H.
Abstract : Abstract: We investigated the efficacy of dietary consumption of Lactobacillus brevis KB290 (KB290) against influenza in humans by a preliminary intervention study on elementary schoolchildren, using a commercially available probiotic drink. Subjects were divided into Groups A and B, and an open‐label, parallel‐group trial was conducted in two 8‐week periods at a 1‐month interval in winter 2013/2014. Group A was provided with a bottle of the test drink containing KB290 (about 6 billion colony‐forming units) every school day in the first period and had no treatment in the second period, and vice versa for Group B. Epidemic influenza was not observed during the first period and only two of 1783 subjects were diagnosed. In the second period, the incidence of influenza in Groups A (no treatment) and B (provided the test drink) was 23·9 and 15·7%, respectively, and the difference was statistically significant ( P < 0·001). The reduction in the incidence of influenza by KB290 consumption was especially remarkable in unvaccinated individuals. This is believed to be the first study to show a probiotic food reducing the incidence of influenza in schoolchildren, although further studies are needed to confirm the effectiveness of the probiotic strain KB290. Significance and Impact of the Study: We demonstrated a reduction in the incidence of influenza in 1089 schoolchildren by continual intake of a probiotic drink containing Lactobacillus brevis KB290 (KB290), isolated from a traditional Japanese pickle 'Suguki'. The effect was especially evident in subjects not inoculated with influenza vaccine. This is believed to be the first report to show reduced incidence of influenza in schoolchildren taking a probiotic food. Further studies are needed to confirm the effectiveness of the probiotic strain KB290, which may be useful in the development of potential anti‐influenza agents derived from common foods.